Just enough math : advanced math for business people to leverage big data - Nathan, Paco (O'Reilly, 2014)
"With the commercial successes of machine learning and cloud computing, many business people need just enough math to take advantage of open source frameworks for big data. This video course from Paco Nathan and Allen Day presents useful areas of advanced math in easy-to-digest morsels. If you're familiar with high school Algebra 2 and basic statistics, you're good to go."--Resource description page.